2020
DOI: 10.3389/fphys.2019.01608
|View full text |Cite
|
Sign up to set email alerts
|

Myokine Regulation of Insulin Secretion: Impact of Inflammation and Type 2 Diabetes

Abstract: Skeletal muscle (SkM) secretes protein factors (myokines) that can exert multiple actions. To study the control of myokine regulation of β-cell function, SkM biopsies were taken from non-diabetic (ND) and Type 2 diabetic (T2D) subjects and satellite cells cultured to myotubes (MT). MT were also treated with lipopolysaccharide (infectious inflammation-II) or a combination of glucose (10 mM), insulin (120 pM), and palmitate (0.4 mM) (metabolic inflammation-MI) to model the inflammatory and metabolic conditions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Further, mitochondrial function within the beta-cell cell may be involved, 28 and muscles may relase cytokines that influence beta-cell mass and/or function. 56 In either case, these studies align with current ACSM and ADA guidelines recommending concurrent training and the inclusion of at least 2 resistance training days in a week, as part of reaching at least 150 min of moderate intensity exercise to impact glycemia.…”
Section: Aerobic Compared With Resistance Exercise For Glycemic Controlsupporting
confidence: 60%
“…Further, mitochondrial function within the beta-cell cell may be involved, 28 and muscles may relase cytokines that influence beta-cell mass and/or function. 56 In either case, these studies align with current ACSM and ADA guidelines recommending concurrent training and the inclusion of at least 2 resistance training days in a week, as part of reaching at least 150 min of moderate intensity exercise to impact glycemia.…”
Section: Aerobic Compared With Resistance Exercise For Glycemic Controlsupporting
confidence: 60%
“…More recently, attention has been raised to a role for skeletal muscle in regulating b-cell mass and function. Conditioned media studies using human T2D skeletal muscle cells have demonstrated that myokines from the skeletal muscle can modulate GSIS in INS-1 832/13 b-cells (46); the presence of myokines could be an explanation for why GSIS was boosted in INS-1 832/13 b-cells treated with CM collected from myotubes overexpressing PAK1. In addition, exercise training has been shown to increase GSIS (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have been conducted on the initial dosage setting of pump insulin in T2DM, and most of these have mainly referred to the normal human insulin secretion mode and the application of patients with T1DM in foreign countries 8 . Previous studies 10 12 have suggested that patients with good reserved β-cell function in the remaining islets would benefit more after intensive therapy. However, there is no simple index for the quantitative evaluation of the function of reserved islets.…”
Section: Discussionmentioning
confidence: 99%